An ice core record of near-synchronous global climate changes at the Bølling transition - Rosen, Julia L.; Brook, Edward J.; Severinghaus, Jeffrey P.; Blunier, Thomas; Mitchell, Logan E.; Lee, James E.; Edwards, Jon S.; Gkinis, Vasileios (Nature geoscience, 2014)
The abrupt warming that initiated the Bølling–Allerød interstadial was the penultimate warming in a series of climate variations known as Dansgaard–Oeschger events. Despite the clear expression of this transition in numerous palaeoclimate records, the relative timing of climate shifts in different regions of the world and their causes are subject to debate. Here we explore the phasing of global climate change at the onset of the Bølling–Allerød using air preserved in bubbles in the North Greenland Eemian ice core. Specifically, we measured methane concentrations, which act as a proxy for low-latitude climate, and the 15 N/ 14 N ratio of N 2 , which reflects Greenland surface temperature, over the same interval of time. We use an atmospheric box model and a firn air model to account for potential uncertainties in the data, and find that changes in Greenland temperature and atmospheric methane emissions at the Bølling onset occurred essentially synchronously, with temperature leading by 4.5 years. We cannot exclude the possibility that tropical climate could lag changing methane concentrations by up to several decades, if the initial methane rise came from boreal sources alone. However, because even boreal methane-producing regions lie far from Greenland, we conclude that the mechanism that drove abrupt change at this time must be capable of rapidly transmitting climate changes across the globe. During the last glacial termination, climate changes associated with the Bølling–Allerød warming were seen throughout much of the Northern Hemisphere. A combination of ice-core records and box modelling shows that this climate change was nearly synchronous across high and temperate latitudes.